An activity-oriented approach towards Portuguese labour inspectors: reconciling compliance, action and innovation - Cunha, L.; Maggioli, S.; Ramos, S.; Guedes, J.; Duarte, D.; Santos Batista, J. (Congress of the Swiss Sociological Association, 2024)
Studies conducted in EU countries have found how inspection and enforcement have a positive impact on OH S compliance and outcomes ( EU OSHA, 2023 20231 However, not much focus has been placed on the i) differen t types of approaches and their impacts; ii) obstacles and opportunities faced by labour inspectors considering the specificities of both their activity and the territory in which they act; or iii) macro challenges which emerge for these professionals ’ practices stemming from demographic and technological transformations For these reasons, u nder the European Agency for Safety and Health at Work ’s (EU OSHA) Call Report on the role of the labour inspectorate and prevention services in supporting OSH compliance in Portugal ””, we are currently conducting research which combines top down (literature and policy analysis) and bottom up (participatory and extended case method) approaches to study the traditional and innovative inspection activities carried out by labour inspection While interviews and focus groups with labour inspectors are still ongoing , the results will allow us t o identify the actors/institutions with which labour inspectors interact ; their perspectives regarding the fragilities and potentialities of the current Portuguese OHS strategy; innovative approaches and/or approach shifts considering technological changes and obstacles opportunities for implementing EU and government recommended practices . Furthermore, this study will also explore how the territorial dimension impacts these results , considering there are more reactive inspections taking place in the northeast when compared to the southeast of the country. In short, despite EU level frameworks, there is limited empirical evidence of what works in practice considering the specificities of labour inspectors’ activity. Insights on these matters are crucial so monitoring and enforcement measures result in sustainable compliance , while also reducing the proportion of reactive inspections.